Pendampingan KALASI (Kenali, Cegah dan Atasi) Penyakit ISPA Pada Orang Tua dan Balita di Desa Wawatu Kecamatan Moramo Utara Kabupaten Konawe Selatan - Majid, Ruslan; Rabbani K, Siti; Meiyana, Putu Eka; Hikmawati, Zainab (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
According to the Southeast Sulawesi Provincial Health Office, the number of ISPA cases in 2021 and 2022 was 115,331, placing it as the top illness in the region. This initiative aims to assist efforts in recognizing, preventing, and addressing ISPA in coastal areas by providing knowledge and skills to the community, particularly parents and toddlers. The implementation method for achieving the objectives of this community service involves a coordinated approach with local district authorities to analyze the situation, gain support, and obtain permission for the activities. This includes providing guidance on how to recognize, prevent, and address ISPA among parents and toddlers in Wawatu Village, North Moramo District, South Konawe Regency. The results of this initiative indicate that there was an increase in respondents' knowledge from pre-test to post-test after receiving education on recognizing, preventing, and addressing ISPA for parents and toddlers. The community was engaged with the educational materials provided, such as booklets, posters, and informational sessions, leading to higher post-test scores, increased enthusiasm for questions, a large turnout, and distribution of booklets and posters to the community